2019
DOI: 10.3390/su11226334
|View full text |Cite
|
Sign up to set email alerts
|

Coopetition in Maritime Tourism: Assessing the Effect of Previous Islands’ Choice and Experience in Tourist Satisfaction

Abstract: Maritime tourism has become a competitive opportunity for many island destinations in search of sustainable development. This article aims to analyze the hypothesis that tourist satisfaction with nautical destinations depends on the experience of previous visits to competing destinations. This hypothesis is relevant in order to ascertain the extent of potential coopetition between tourist destinations from the point of view of the consumers. This may ask for the need of cooperation within the competitive envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(112 reference statements)
0
11
0
2
Order By: Relevance
“…They were published in the last 5 years and were considered the most cited and relevant. [ [90][91][92][93] The 25 selected articles were divided into five research areas using content analysis: "Perceived Sustainability and Tourist Behavior", "Destination and Place Branding", "Destination Management", "Ecotourism and Rural Tourism" and "Maritime and Island Tourism". The objective is to capture the gaps and objectives they intend to fulfill.…”
Section: Analysis Of Research Opportunitiesmentioning
confidence: 99%
“…They were published in the last 5 years and were considered the most cited and relevant. [ [90][91][92][93] The 25 selected articles were divided into five research areas using content analysis: "Perceived Sustainability and Tourist Behavior", "Destination and Place Branding", "Destination Management", "Ecotourism and Rural Tourism" and "Maritime and Island Tourism". The objective is to capture the gaps and objectives they intend to fulfill.…”
Section: Analysis Of Research Opportunitiesmentioning
confidence: 99%
“…In this way, groups, institutions and cities express ideas, ambitions, and intentions captured in the distinctive design of their buildings that could encourage tourists to come and revisit the attraction site. Island tourism that involves activities related to the value placed on the arts and architecture of the place is considered an economic catalyst for coastal destinations due to its high multiplier effect on employment, ease of integration into the traditional tourist offers and the boosts it gives to the qualification of the coastlines and innovation (Lam-Gonzalez et al, 2019). Lam-Gonzalez et al (2019) stated that developing island networking structures through infrastructure, cultural assets, natural environments, and promotion could increase island destinations' competitiveness.…”
Section: Art/architecture and Satisfactionmentioning
confidence: 99%
“…There have also been studies that evaluated the constraints on nautical tourism (Jovanovic et al, 2013) and dimensions of yachting tourism experiences (Mikulić et al, 2015;Pipere et al, 2020). However, very few studies have examined sailing tourist satisfaction, and the impacts of marina attributes on sailing tourism experience (González et al, 2018;Lam-González et al, 2019a, 2019b. González et al (2018) examined the relationship between the weather and the number of nautical activities by using the ordinal logistic regression model.…”
Section: Sailing Tourismmentioning
confidence: 99%
“…Similar to González et al's (2018) research, Lam-González et al (2019a found a significantly positive relationship between climatic experience and tourists' satisfaction. In another research, Lam- González et al (2019b) investigated tourist satisfaction with visiting Cape Verde and concluded that previous satisfactory travel experience leads to higher satisfaction levels with the sailing destination of Cape Verde. Lam- González et al (2020) also proposed that the quality of sailing tourism and the diversity of cultural offers increase tourist satisfaction.…”
Section: Sailing Tourismmentioning
confidence: 99%